Implementasi Eco-Innovation dan Sustainable Manufacturing terhadap Pertumbuhan Ekonomi Sirkular UMKM Di Kota Langsa - Lubis, Nurliza; Faridy, Najihatul (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study aims to determine the implementation of Eco-Innovation and Sustainable Manufacturing on the Circular Economic Growth of MSMEs in Langsa City. This study uses quantitative research. Data collection by conducting surveys and questionnaires. The number of respondents is 100 people consisting of MSMEs in the food and beverage sector in Langsa City. Questionnaire data was tested using SPSS Version 23. The data analysis technique used linear regression analysis. The implementation of Eco-innovation is relatively small in influencing the circular economy. However, if the individual influence on the circular economy is tested, partially Eco-Innovation has not had an influence on the circular economy. However, if tested by multiple linear regression, Eco-Innovation still has hope in increasing the circular economy of MSMEs by 25%. If tested individually, Sustainable Manufacturing has a significance value of 0.00 <0.05. The conclusion of the hypothesis research is accepted because Sustainable Manufacturing has an effect on the circular economy. Likewise, the results of the multiple linear regression of Sustainable Manufacturing have a regression coefficient of 0.620. A positive coefficient means that every 1% increase in Sustainable Manufacturing will increase the Circular Economy by 62%. The recommendation of the research results requires a deeper study of eco-innovation in the production sector.